Effect of pharmacist-led patient education on adherence to tuberculosis treatment - RABUŞ, ŞULE (AMER SOC HEALTH-SYSTEM PHARMACISTS, 2007)
Purpose. The purpose of this study was to assess the effect of a clinical pharmacist-directed patient education program on the therapy adherence of first-time tuberculosis (TB) patients and to identify the major pharmaceutical care needs and issues of first-time TB and multidrug-resistant (MDR)-TB patients. Methods. In the first part of the study, first-time TB patients were randomized either to the No EDU group (n = 58) where patients received routine medical and nursing care or to the EDU group (n = 56) where patients were also provided with clinical pharmacist-directed patient education. The patient's adherence to treatment was evaluated by attendance at scheduled visits, medication counting, and urine analysis for the presence of isoniazid metabolites. In the second part of the study, the pharmaceutical care needs and issues were determined for first-time TB patients and for MDR-TB patients (n = 40). Results. The adherence of patients who received pharmacist-directed patient education was greater than that of patients who did not. The attendance at scheduled visits and urine analysis for the presence of isoniazid metabolites yielded better results in respect to adherence for the EDU group (p < 0.05), while medication counting did not differ between the two groups. The major pharmaceutical care needs of first-time TB patients were for pain control, nutrient replacement, appropriate prescribing, respiratory control, and diabetic control. Similar findings were recorded for MDR-TB patients. Conclusion. Patients' adherence to TB treatment improved when a pharmacist provided patient education on medication use and addressed patients' pharmaceutical care issues.
Keywords: antituberculars; clinical pharmacists; compliance; isoniazid; patient information; patients; pharmaceutical care; rational therapy; resistance; tuberculosis; MULTIDRUG-RESISTANT TUBERCULOSIS; DRUG; PROSPECTS; THERAPY; SMOKING; PROGRAM; TURKEY; URINE